Anterior cruciate ligament injury is unlikely to occur when performing a stable weight lifting operation - Moon, Y.; Moon, J. (Korean Journal of Sport Biomechanics, 2018)
Objective: The purpose of this study was to examine the effect of increase in barbell weight on closely related variable to the anterior cruciate ligament (ACL) injury which are knee joint kinematics, joint load, joint moment, and maximum load attainment point during snatch of the weight lifting.